The Approach of Abi Abd al-Rahman Ismail al-Darir al-Nisaburi in the interpretation of the verses of Rulings in his interpretation (Adequacy in Interpretation) - Analytical study (Islamic Sciences Journal, 2023)
The Holy Qur’an is the first legislative source for the verses of the rulings. There are noble verses in its great surah that dealt with various aspects of the lives of Muslims. The interpretations of the verses of the rulings had a great impact in directing the rulings of Islamic jurisprudence and its principles, especially since the interpreters’ approaches varied in dealing with the interpretation of the verses of the rulings. Intolerance to a specific group and defended it, some of which expanded and compared the schools of jurisprudence, and some of them dealt with the interpretation of verses in their Qur’anic context. (d. 430 AH) in his interpretation (Enough in Interpretation). The aim of which was to direct consideration of how to study the verses of rulings in the Noble Qur’an by deducing legislative jurisprudence rulings, and the research was divided into three demands: The first requirement: the definition and interpretation of the Nesaburi blind, the second requirement: A Brief on the Verses of Judgments and the Differences of Scholars in Their Judgment, The Third Requirement: The Approach of the Blind Nesaburi in Interpreting Verses of Judgments in (Sufficiency in Interpretation).
Keywords: Approach, Al Darir, verses, rulings, sufficiency